Funcionalização química de nanofibrilas de celulose com haleto orgânico e hidrogenossulfato - Jesus Barros, Marcus Felippe de (2022)
Belonging to the chemical group of carbohydrates and considered the main component of the plant cell wall, ensuring protection and support for the development of vegetables, cellulose is the most abundant biopolymer on Earth. Cellulose nanofibrils (CNFs), possessing unique properties, has stood out due to its abundance, because it is biodegradable, has good mechanical, optical and thermal properties. Has high surface area specific with hydroxyl functional groups that allows various chemical modifications to improve the physical-chemical properties of existing materials and/or develop new materials. Therefore, the objective of this work is the chemical functionalization of CNFs with the reagents 2-chloroethylamine hydrochloride and the 2-aminoethyl hydrogen sulfate for future application as filter membranes. The functionalized nanofibrils were characterized via Fourier transform infrared spectroscopy (FTIR), potentiometric titration, X-ray diffraction (XRD) and atomic force microscopy (AFM). The low value of the percentage of nitrogen and the degree of substitution characteristic of this type of reaction were calculated from the potentiometric titration. The results indicate that the chemical modification reaction under inert atmosphere was successful in finding bands in the FTIR spectrum characteristic of chemical modification. Through the XRD technique it was verified that the crystallinity indices decreased and the AFM micrographs found that there was a decrease in the diameter of the nanofibrils after the chemical modification reactions in the CNFs.